MENJUAL WANITA HIBURAN: PEMBENTUKAN CITRA SEKSUAL PEREMPUAN DALAM CERPEN PADA MAJALAH HIBURAN TERBITAN 1950-1965 - Formas Juitan Lase (Program Studi Ilmu Komunikasi Universitas Paramadina, 2015)
This article will elaborate about how the entertainment magazine in Indonesia between 1950 until 1965 shaped the woman‟s image as a “comfort women” in their short stories. This research used the qualitative methods combined with structure analysis, with the main finding that women being reproduced as a source of „enjoyment‟ through the imagery of woman character in the short stories with three categories such as : woman as a seducer, woman as a spectacle, and woman as a „keeper‟ of man‟s spirit in the time of war. Woman being stereotyped as a weak and submissive into the man‟s will, through the sexual myths as if this myths perceived as a truth. On the other hand, the woman figure being identified with passion, sexually active, and aggressive. The entertainment magazine produced the image of woman in vain, that woman always surrenders herself in the ownership of man. This image later became the standardization of the entertainment genre at that time. This imagery also affirmed that the power relations of media through the editorial staff preferences always contained with the male bias, thus, represented the patriarchal view in which it sees woman as an „entertainer‟. Keywords: Bitchy, Power, Patriarchy and Entertainment Magazines